The Influence Of Selection And Recruitment On Employee Performance PT. Abon Sapi 32 Tasikmalaya - Ramdhani A, Naufan; Barlian, Barin; Yuniar, Evilia Sri (Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to determine the effect of selection on employee performance and the effect of recruitment on employee performance on employees of PT Abon Sapi 32 Tasikmalaya with a total population of 40 employees. The research method used is the explanatory survey method, while the sample withdrawal technique uses saturated sample technique. So that the sample used was 40 people. The data source used is primary data source and the data is collected through questionnaires, interviews and observations. In this study, the analysis tool used path analysis with multiple linear regression analysis. In the hypothesis testing process using the F test and t test. The results showed that the Selection, Recruitment and Employee Performance of PT Abon Sapi 32 had a very good assessment classification. Selection and Recruitment simultaneously have a significant effect on the performance of employees of PT. Abon Sapi 32. Selection partially has a significant effect on the performance of employees of PT. Abon Sapi 32. Recruitment partially has a significant effect on the performance of employees of PT. Abon Sapi 32.